Towards a Sequential One‐Pot Preparation of 1, 2, 3‐Benzotriazin‐4(3H)‐ones Employing a Key Cp*Co(III)‐catalyzed C−H Amidation Step. Issue 12 (26th April 2018) - Chirila, Paula G.; Skibinski, Lauren; Miller, Keith; Hamilton, Alex; Whiteoak, Christopher J.
Abstract: 1, 2, 3‐benzotriazin‐4(3 H )‐one derivatives have been recognised for their potential application as pesticides and pharmaceuticals and new methodologies for their preparation, starting from readily accessible reagents would therefore be an attractive proposition. A wide range of differently substituted benzamides are readily available, which provide an excellent substrate scaffold for the application of direct C−H functionalization protocols. In this context, herein we report the use of a Cp*Co(III) catalyst for the amidation of these benzamides, using 1, 4, 2‐dioxazol‐5‐ones as amidating agent. The isolable intermediate 2‐acetamido benzamide products can thereafter be converted to the desired 1, 2, 3‐benzotriazin‐4(3 H )‐one derivatives through the use of tert ‐butyl nitrite under mild conditions. It was found to be possible to perform the second step with the crude reaction mixture obtained from the initial C−H amidation step, leading to the overall development of a facile one‐pot procedure for the preparation of a range of substituted 1, 2, 3‐benzotriazin‐4(3 H )‐one derivatives, requiring only 5 hours of reaction time, which is also applicable on a gram scale. In addition, the key Cp*Co(III)‐catalyzed C−H amidation step has been studied by DFT calculations in order to fully elucidate the mechanism. Abstract :